Mapping Slip Trip & Fall and Crowd Crush Hazards at Fisherman's Wharf: A Triangulation of Physical, Observational, and Survey Data - Alicya Rosa Kumalaratri; Lukmandono Lukmandono; Po Hsiang Liu; Yoniv Erdhianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
Fisherman’s Wharf in Tamsui, Taiwan, is a popular coastal tourist destination that attracts large numbers of visitors, increasing the likelihood of Slip, Trip and Fall (STF) and Crowd Crush hazards. This study evaluates risk levels, examines hazard-generating activities, and identifies the root causes of risk to develop more effective and sustainable control measures. It integrates Hazard Identification and Risk Assessment (HIRA), Job Safety Analysis (JSA), and Root Cause Analysis (RCA) within a comprehensive risk assessment framework. Data derive from 300 hours of field observation, visual documentation, and a survey of 96 respondents, including visitors, employees, and site managers. HIRA assesses risk levels and identifies priority areas, JSA examines high-risk activities, and RCA investigates the underlying causes of risk. The results show that Zone C (Floating Pier and Stairs) presents the highest STF risk, with a HIRA score of 12 (High Risk), while Zone B (Lover’s Bridge) records the highest Crowd Crush risk, with a HIRA score of 16 (High Risk). Walking on damp and slippery surfaces emerges as the principal contributor to STF incidents. In contrast, visitor congestion, two-way pedestrian flows, and the tendency of visitors to stop for photographs drive Crowd Crush risks. RCA findings highlight several key root causes, including inadequate anti-slip surface treatments, insufficient preventive facility inspections, and ineffective crowd management practices. These findings underline the need to upgrade physical infrastructure, improve visitor flow management, and strengthen safety systems through systematic near-miss monitoring and reporting.